2015
DOI: 10.1039/c5ta00843c
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Sn-doped LiTi2(PO4)3/C nanofibers for ultra-fast charging and discharging

Abstract: 1 Sn-doped LiTi 2 (PO 4 ) 3 /C composite nanofibers are synthesized by a facile 2 electrospinning process. The unique one dimensional nanostructure combined with 3 uniform electrically conductive carbon matrix allows high-rate transportation of 4 lithium ions and electrons. Besides, Sn-doping could further decrease electrochemical 5 resistance. Sn-doped LiTi 2 (PO 4 ) 3 /C composite nanofibers exhibit excellent 6 electrochemical performance, especially the ultra-fast charging/discharge capability. 7 At a charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 29 publications
1
4
0
3
Order By: Relevance
“…颗粒纳米化是提升电极材料电化学性能的重要 思路 [55][56][57][58][59] 。当材料粒径达到纳米尺度时, 能够有效缩 短 Li + 的扩散路径, 同时抑制缺陷的阻碍作用, 控制 极化现象, 另一方面, 纳米尺度的材料具有较大的 比表面积, 可以增大电极/电解液界面, 进而增加反 应活性位点, 因此颗粒纳米化可以提高材料的倍率 性能和可逆容量 [60] 。纳米尺度的 LiTi 2 (PO 4 ) 3 颗粒主 要通过溶胶-凝胶法、水热法等液相方法合成。 颗粒形貌控制是提高电极材料电性能的另一重 要思路。为获得具有特定形貌的颗粒往往需要采用 水/溶剂热法、静电纺丝法和模板法。Liang 等 [44] 采用 水热法, 在 220 ℃下保温 48 h 合成了具有规则立方 形貌的 LiTi 2 (PO 4 ) 3 , 随着时间延长和温度升高, 颗粒 的微观形貌逐渐呈现规则的方块形状, 最大颗粒接 近 50 μm。Deng 等 [61] 采用溶剂热法合成了具有规则 立方形貌的 LiTi 2 (PO 4 ) 3 , 其粒径尺寸约为 200 nm。 在 10C 倍率下, 其全电池体系 LiTi 2 (PO 4 ) 3 |1 mol•L -1 LiTFSI|LiMn 2 O 4 经 1000 次循环, 容量保持率约为 80%。Liu 等 [24] 将原料置于静电纺丝仪中, 获得了纤 维状前驱体, 经煅烧后获得 LiTi 2 (PO 4 ) 3 纤维材料, 其流程如图 4(a)所示。 与相应的颗粒材料相比, 纤维材料具有比表面 积大和长径比高等优点, 能够有效缩短 Li + 的迁移 距离, 增大材料和电解液的接触面积, 有利于电化 学反应, 展现出更优秀的倍率性能, 由图 4(b)可知, 纤维材料的倍率性能明显优于相应的颗粒材料。…”
Section: 颗粒纳米化及形貌控制unclassified
See 2 more Smart Citations
“…颗粒纳米化是提升电极材料电化学性能的重要 思路 [55][56][57][58][59] 。当材料粒径达到纳米尺度时, 能够有效缩 短 Li + 的扩散路径, 同时抑制缺陷的阻碍作用, 控制 极化现象, 另一方面, 纳米尺度的材料具有较大的 比表面积, 可以增大电极/电解液界面, 进而增加反 应活性位点, 因此颗粒纳米化可以提高材料的倍率 性能和可逆容量 [60] 。纳米尺度的 LiTi 2 (PO 4 ) 3 颗粒主 要通过溶胶-凝胶法、水热法等液相方法合成。 颗粒形貌控制是提高电极材料电性能的另一重 要思路。为获得具有特定形貌的颗粒往往需要采用 水/溶剂热法、静电纺丝法和模板法。Liang 等 [44] 采用 水热法, 在 220 ℃下保温 48 h 合成了具有规则立方 形貌的 LiTi 2 (PO 4 ) 3 , 随着时间延长和温度升高, 颗粒 的微观形貌逐渐呈现规则的方块形状, 最大颗粒接 近 50 μm。Deng 等 [61] 采用溶剂热法合成了具有规则 立方形貌的 LiTi 2 (PO 4 ) 3 , 其粒径尺寸约为 200 nm。 在 10C 倍率下, 其全电池体系 LiTi 2 (PO 4 ) 3 |1 mol•L -1 LiTFSI|LiMn 2 O 4 经 1000 次循环, 容量保持率约为 80%。Liu 等 [24] 将原料置于静电纺丝仪中, 获得了纤 维状前驱体, 经煅烧后获得 LiTi 2 (PO 4 ) 3 纤维材料, 其流程如图 4(a)所示。 与相应的颗粒材料相比, 纤维材料具有比表面 积大和长径比高等优点, 能够有效缩短 Li + 的迁移 距离, 增大材料和电解液的接触面积, 有利于电化 学反应, 展现出更优秀的倍率性能, 由图 4(b)可知, 纤维材料的倍率性能明显优于相应的颗粒材料。…”
Section: 颗粒纳米化及形貌控制unclassified
“…根据前驱体的种类, 含碳试剂可分为有机碳源 和无机碳源。在高温裂解时, 有机碳源可形成同质化 碳层, 其碳层厚度易于控制, 但石墨化程度通常难 以控制, 无机碳源有助于形成 3D 导电网络结构, 但 对单一颗粒的表面包覆可能效果不佳, 因此同时引 入有机和无机碳源可以提供互补优势 [68] 。有机碳源 主要包括柠檬酸、葡萄糖、蔗糖、淀粉和聚乙烯醇 等, 无机碳源主要有乙炔黑、石墨烯和碳纳米管 (Carbon nanotubes, CNTs)等。 图 4 静电纺丝法示意图(a), LiTi 2 (PO 4 ) 3 纤维与颗粒的倍率性能曲线(b) [24] Fig. 4 Schematic diagram of electrospinning (a), comparison of rate performance between LiTi 2 (PO 4 ) 3 fibers and particles (b) [24] 第 5 期 王禹桐, 等: 水系锂离子电池负极材料 LiTi 2 (PO 4 ) 3 的研究进展 487…”
Section: 碳源对 Liti 2 (Po 4 ) 3 电化学性能的影响unclassified
See 1 more Smart Citation
“…More recently, graphene [62] and carbon nanotube [63] were successively incorporated to LiTi 2 (PO 4 ) 3 , and excellent cycling stability and high rate performance were also presented. Liu et al [64] synthesized Sn-doped LiTi 2 (PO 4 ) 3 /C composite nanofibers via electrospinning method, which delivered the capacity of 101.7 mA g −1 at 4 A g −1 with capacity retention of 99.5 mA g −1 after 10 0 0 cycles, and its capacity retention can reach 66.2% even at high rate of about 600 C (6 s). Wang and co-workers [65] reported that Na doping can increase lattice volume and enhance the diffusion of lithium ions.…”
Section: Polyanionic Materialsmentioning
confidence: 99%
“…NASICON-type anodic LiTi 2 (PO 4 ) 3 and cathodic Li 3 V 2 (PO 4 ) 3 are made of environmentally friendly materials. In addition, they are constructed by stable lattice structures consisting of three-dimensional pathways for Li + transportation, which enable negligible (de)­intercalation strain and fast transportation of Li + while cycling, leading to good rate performance and extended cycle life. , The intrinsically poor electronic conductivity of NASICON-type materials can be mitigated by elemental doping, optimization of particle size, or surface modification in terms of carbon coating. Regarding the flexibility of electrodes, instead of using a large amount of nonconductive binders, the recent research trend is to fabricate electrodes that possess high specific energy density and flexibility in novel geometric designs without the application of carbon additives, binder, or even conventional metallic current collectors. Such an electrode is usually made of active material combined with graphene or carbon nanotubes (CNTs) and feature a high in-plane electrical conductivity, an outstanding tensile modulus, and great mechanical endurance. The elastic feature of carbon-based fabrics can also eliminate the influence caused by volume variations of embedded active materials during charge–discharge and thus preserve the microstructure of electrodes from deformation caused by internal strain . Comparing the application of CNT fabric with graphene in flexible electrodes, advantages of low cost, high flexibility, being substrate-free, and sufficient content of graphitized carbon make CNT fabric highly competitive for large-scale production.…”
Section: Introductionmentioning
confidence: 99%